Pelatihan Kecerdasan Buatan Untuk Mendukung Kegiatan Belajar Mengajar Guru Ma Nwdi Kelayu - Mandala Putra, Hadian; Wahidah, Ida; Iman Darmawan, Muhammad; Nuzuluddin, M (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
This Community Service Program focuses on training teachers at Madrasah Aliyah NWDI Kelayu to utilize artificial intelligence and cloud technology to support teaching and learning activities. In the Society 5.0 era, the ability to integrate modern technology into education is crucial. This program aims to enhance teachers' competencies in adopting technologies such as Gamma, Question Well, and ChatGPT, and utilizing Google services like Google Drive and Google Forms. The training was conducted intensively through theoretical and practical sessions designed to strengthen teachers' technical understanding and skills. The results of this training indicate a significant improvement in teachers' ability to implement technology in the learning process. Trained teachers are now capable of using these technologies to create more interactive and efficient learning experiences, which, in turn, are expected to improve student outcomes. This program is also expected to serve as a model for similar initiatives in other schools aiming to adopt technology in education